Phrasing Homer: A Cognitive-Linguistic Approach to Homeric Versification. Issue 1 (1st January 2020) - Janse, Mark
Abstract : Anyone interested in the colometry or "inner metrics" of the Homeric hexameter is confronted with a wide variety of different approaches, favouring two-, three- or four-colon verses or any combination of these. This article builds on Egbert Bakker's interpretation of Homeric discourse as a succession of intonation / information units (IUs). Its aim is to provide more secure cognitive-linguistic criteria for determining caesura positions and the resulting cola / IUs.